Atomically Defined Monocarborane Copper(I) Acetylides with Structural and Luminescence Properties Tuned by Ligand Sterics. Issue 37 (6th May 2019) - Zhang, Kang; Shen, Yunjun; Yang, Xiaoli; Liu, Jiyong; Jiang, Tao; Finney, Nathaniel; Spingler, Bernhard; Duttwyler, Simon
Abstract: The weakly coordinating cluster [CB11 H12 ] − is used as a versatile building block for the preparation of luminescent copper(I) complexes. Treatment of [CB11 H11 ‐12‐C≡CH] − with CuI and ammonia affords {(CB11 H11 ‐12‐C≡C)2 Cu4 (NH3 )3 } n (2 ). Addition of selected phosphine and pyridine ligands transforms 2 to a range of homometallic products 3 –13 . All compounds have been characterized by X‐ray crystallography, which reveals a surprising variety of structural complexity featuring cores with two to ten Cu + centers. In the solid state, products 3 –13 exhibit room‐temperature phosphorescence across the visible spectrum in colors from blue to deep red. Lifetimes at room temperature are in the microsecond regime, and quantum yields of up to Φ=0.99 are observed. Abstract : The carborane cage [CB11 H12 ] − is used as a versatile building block for the preparation of luminescent copper(I) complexes. The compound {(CB11 H11 ‐12‐C≡C)2 Cu4 (NH3 )3 } n is transformed to homometallic products 3 –13 bearing simple phosphine or pyridine ligands, all of which have been characterized by X‐ray crystallography. Complexes 3 –13 exhibit room‐temperature phosphorescence across the visible spectrum in colors from blue to deep red.